1999
DOI: 10.1002/(sici)1521-3951(199910)215:2<1145::aid-pssb1145>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Magnetoresistance Effects at Low Temperature in Silver Telluride Thin Films

Abstract: We report the low temperature abnormal longitudinal magnetoresistance (MR) in self‐doped silver telluride films. We observe the large negative MR and multi‐peaks of magnetic resistivity ρ and MR in the Ag2.1Te films, which strongly depends on doping concentration and temperature. The origin of the abnormal MR behavior is tentatively ascribed to the complex structure and texture of the films and is discussed by means of the formation of impurity bands in the films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A material with silver atoms shows an anisotropic negative MR behavior and a system with small silver clusters shows a linear positive MR effect. For silver-rich silver telluride-a system with comparable thermodynamic, kinetic, and microstructural properties-Liang et al 8 found also a negative MR effect.…”
Section: Introductionmentioning
confidence: 99%
“…A material with silver atoms shows an anisotropic negative MR behavior and a system with small silver clusters shows a linear positive MR effect. For silver-rich silver telluride-a system with comparable thermodynamic, kinetic, and microstructural properties-Liang et al 8 found also a negative MR effect.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the MR of Ag 2+δ Se and Ag 2+δ Te samples exhibits a linear dependence on the magnetic field from 1 mT to 5.5 T. Chuprakov and Dahmen then reported a large positive MR effect in the thin film of Ag 2−δ Te with Te excess [2]. Many researchers have carried out experiments [3][4][5][6][7][8][9][10][11][12] to verify the results of Xu and Chuprakov. Driven by the experimental results, theory researchers proposed models to interpret the unusual linear MR effect of Ag 2+δ Se and Ag 2+δ Te materials. Abrikosov predicted a quantum linear MR effect for specific materials which required the matrix to be a gapless semiconductor with a linear energy spectrum [13,14].…”
Section: Introductionmentioning
confidence: 99%